Orientations of Mistaken Point Fronds Indicate Morphology Impacted Ability to Survive Turbulence - Vixseboxse, Philip B.; Kenchington, Charlotte G.; Dunn, Frances S.; Mitchell, Emily G. (Frontiers in Earth Science, 2021)
The Ediacaran organisms of the Mistaken Point E surface have provided crucial insight into early animal communities, including how they reproduced, the importance of Ediacaran height and what the most important factors were to their community dynamics. Here, we use this iconic community to investigate how morphological variation between eight taxa affected their ability to withstand different flow conditions. For each of Beothukis, Bradgatia, Charniodiscus procerus, Charniodiscus spinosus, Plumeropriscum, Primocandelabrum and Fractofusus we measured the orientation and length of their stems (if present) and their fronds. We statistically tested each taxon’s stem and frond orientation distributions to see whether they displayed a uniform or multimodal distribution. Where multimodal distributions were identified, the stem/frond length of each cohort was tested to identify if there were differences in size between different orientation groups. We find that Bradgatia and Thectardis show a bimodal felling direction, and infer that they were felled by the turbulent head of the felling flow. In contrast, the frondose rangeomorphs including Beothukis, Plumeropriscum, Primocandelabrum, and the arboreomorphs were felled in a single direction, indicating that they were upright in the water column, and were likely felled by the laminar tail of the felling flow. These differences in directionality suggests that an elongate habit, and particularly possession of a stem, lent greater resilience to frondose taxa against turbulent flows, suggesting that such taxa would have had improved survivability in conditions with higher background turbulence than taxa like Bradgatia and Thectardis, that lacked a stem and had a higher centre of mass, which may have fared better in quieter water conditions.